Higher Preoperative Endometrial Cancer Risk Showed More Advanced Stage - Jasmine Iskandar; Gregorius Tanamas; Tofan W. Utami; Tricia D. Anggraeni,; Â Kartiwa H. Nuryanto (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To evaluate the pr eoperative endo metria l cancer risk as a guida nce to choose th e typ e of surg ical approach based on European Society for Medical Oncology guideline (200 9). Method: Cross-sectional study involved 73 endometrial cancer patients of Dr. Cipto Mangunkusumo Hospital, from january 200 6 to December 2012 whi ch obt ain ed from medical record. The inclusion criteria wer e endometr ial cancer pati ents with compl ete D&C, ultr asonographic, and postoperative histopathological rep orts. Endometrial cancer risk of recurren ce was classified acco rding to ESMO 2009 and final diagno sis and stage based on FIGO. Result: From 40 5 patients, only 73 patients had compl ete reports. Most of the them were postmenopaus al (54.8 %), non-nulliparity (79 .9%), and obese (49.5%) women.According to risk of recurren cestratification, low, intermediate and high risk were found in 12 patients, 27 patients, and 34 pati ents. Based on FIGO, there were 60.2% early and 39.8% advanced sta ge. In high risk gro up, rates of advan ced stage wer e prominent compar ed to othe r gro ups. There were 38.3% patients with postoper ativ e positive lymph nod es metastases. Conclusion: Most of th e endometrial cancer patients we re pr eoperatively diagnosed as high risk. The commones t stage after surgical examination were me. High risk of recurrence showed more positive lymph node compared to low or intermediat e risk. Result of preoperative histopathological and myometrial invasion compared to postoper ative results wer e showed to be inconsistent Pat ients with =1/2 myometrial invasion had more positive lymph nodes metastases. Endometrial cancer risks compared to FIGO stage showed the higher the risk, th e more advanced the stage were. Keywords: endometrial cancer, FIGO stage, high risk, histol ogical type, intermediate risk , low risk, lymph node.